THE LATE RIPHEAN MIROEDIKHA MICROBIOTA FROM SIBERIA. COMMUNICATION 2: INTERPRETATION IN TERMS OF BIOTIC PALEOSUCCESSION - Veis A.F.; Petrov P.Yu.; Vorob'eva N.G. (My University, 1999)
Changes in the abundance and taxonomic composition of organic-walled microfossil assemblages of the Late Riphean Miroedikha microbiota, one of most diverse and thriving in the Proterozoic, were analyzed at ten discrete stratigraphic levels. The revealed time succession of these assemblages can be considered as an analogue of Phanerozoic coenogenic paleosuccessions characterizing the evolutionary trend from pioneer to postpioneer and climax communities. Some peculiar features of Riphean paleosuccessions and difference in diversity dynamics of morphotypes characteristic of microbiota at the transgressive and regressive stages of sedimentation are outlined. It is noted that consecutive taxonomic changes at these stages are comparable with coenogenic paleosuccessions of the migration and mutation types, and these transformations in microbiotas of the Riphean time apparently were related to the first-order evolutionary cycles of paleobasins. The suggested synoptic model of the Miroedikha microbiota "ontogeny" is important for understanding the progressive complication of the Precambrian microbes.
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей